Persatuan Pemuda Muslim Se-Eropa: Its Qualified Founders, Progression and Nature - S. Sujadi (Al-Jami'ah: Journal of Islamic Studies, 2010)
This article concentrates on the history of Persatuan Pemuda Muslim se-Eropa (PPME, Young Muslims Association in Europe), depicting its founders’qualifications, historical founding, and nature, which has been against practical politics, and restructure and expansion. This association remains the largest Indonesian Islam-oriented Muslim association in Europe. However, there has been little research done on this association, despite its significant contributions to the socio-cultural and religous activities of Indonesian Muslims in Europe, particularly in the Netherlands and Germany. Therefore, this article aims to fill the gap in academic research, dealing with its creation and  development up till the present. To deal with this subject, a historical method emphasizing a chronological approach is applied. In addition to historical evidence, oral sources were primarily used due to the scarcity of written documents.